Combined endoscopic approaches in management of complicated forgotten double J stent: A case report - Giri, Ganesh Kumar; Khadka, Tunam; Sherpa, Pasang; Pradhan, Erena; Adhikari, Aayam; Paudyal, Prajwal (Journal of Kathmandu Medical College, 2023)
Forgotten Double J (DJ) ureteric stent with encrustation is a source of morbidity and unrequired admission. It is prevalent due to a lack of patient education and follow-up in third-world countries like Nepal. A case is reported of 30 years gentleman who had underwent right pyelolithotomy for large staghorn calculus and placement of DJ stent after surgery. The patient presented with encrusted, retained DJ stent which was managed with endoscopic combined intrarenal surgery with retrieval of the forgotten DJ stent.